Ocular motor score a novel clinical approach to evaluating ocular motor function in children - Olsson, Monica; Fahnehjelm, Kristina Teär; Rydberg, Agneta; Ygge, Jan (Acta ophthalmologica (Oxford, England), 2013)
. Purpose:  Ocular motility disturbances are common in a number of neuropaediatric and neurometabolic disorders. Assessment of ocular motor function can be a source of information for diagnosis and follow‐up of these patients. Aim:  To evaluate a new clinical ocular motor function test: ocular motor score (OMS) and provide reference values in children and young adults without known ocular or neurological disorders. Material and Methods:  A total of 233 children and young adults, 103 males and 130 females between the ages of 6 months and 19 years, were assessed according to a specific OMS protocol. They were divided into four different age groups: 0.5–3, 4–6, 7–10 and 11–19 years. The OMS protocol consists of 15 different subtests evaluating ocular motor function, and a total score of minimum 0 up to max 15 can be obtained: the minimum score, 0, is considered normal while 1 represents an abnormal function. Results:  The median OMS in the whole reference group was 0.3 (range 0–4.8). The median OMS in the different age groups, starting with the youngest, was: 0.9 (range 0.3–4.8), 0.3 (range 0–3.4), 0.3 (range 0–2.3) and 0 (range 0–3.5), respectively. The youngest subjects, aged 0.5–3, showed a significantly higher total OMS compared with the other age groups (p < 0.001). Conclusion:  This study provides reference values for the OMS test in a population aged 0.5–19 years. The test may be valuable as a screening tool for identification and follow‐up of ocular motor dysfunction in children and young adults.